A sandbox regulatory framework for bullion integration in the decentralised digital finance (DeFi) ecosystem - Aidatul Fitriyah; Beckham Napitupulu (Journal of Entrepreneurial Economics, 2026)
Background: This research addresses regulatory friction and systemic risks arising from the integration of tokenised bullion into the Decentralised Finance (DeFi) ecosystem, focusing on how to balance investor protection with continued innovation. It outlines the context of DeFi’s permissionless architecture, the sensitivity of bullion as a high value asset class, and the resulting challenges for regulatory certainty and market integrity. Methods: The study employs an analytical and conceptual approach based on a comprehensive literature review and the examination of international regulatory frameworks, including IOSCO principles and FATF recommendations. It develops an adaptive regulatory model by comparing existing rules on securities, commodities, and virtual assets with the specific risk profile of tokenised bullion in DeFi. Findings: The analysis identifies core conflicts between DeFi’s borderless, permissionless protocols and jurisdiction bound AML/KYC requirements, as well as single point of failure risks arising from custodial bullion structures. To address these conflicts, the paper proposes a DeFi Bullion Specific Regulatory Sandbox Framework grounded in technology neutral and risk based principles, which embeds regulatory KPIs, capital adequacy thresholds, and RegTech enabled real time monitoring. Conclusion: The results indicate that the proposed sandbox model offers a viable pathway to mitigate systemic risk and enhance regulatory certainty by enforcing compliance at critical on chain and off chain interaction points, particularly physical redemption of bullion. The framework strengthens investor protection while preserving space for innovation in tokenised bullion markets. Novelty/Originality of this article: This research delivers a comprehensive and actionable regulatory blueprint tailored to tokenised bullion in DeFi, explicitly addressing jurisdictional arbitrage and dual asset integrity issues. Its original contributions include defining technical prerequisites for embedding AML compliance into DAO governance and outlining a cross border mandatory liquidation protocol as a theoretical roadmap for regulators and industry stakeholders.